2013
DOI: 10.3386/w19544
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Micro and Macro Expenditure Measures Across Countries Using Differing Survey Methods

Abstract: At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w19544.ack NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 9 publications
4
28
0
Order By: Relevance
“…The top left panel shows coverage rates for total spending (including medical) which decline faster in the UK than the US. 15 These fall from 80% to 71% in the UK over the Barrett et al (2015). The primary difference is that medical spending is not removed from total spending here but is removed in Barrett et al 16 These figures are obtained by taking the proportional change in coverage (i.e.…”
Section: Appendix A: the Within Period Demand Systemmentioning
confidence: 99%
“…The top left panel shows coverage rates for total spending (including medical) which decline faster in the UK than the US. 15 These fall from 80% to 71% in the UK over the Barrett et al (2015). The primary difference is that medical spending is not removed from total spending here but is removed in Barrett et al 16 These figures are obtained by taking the proportional change in coverage (i.e.…”
Section: Appendix A: the Within Period Demand Systemmentioning
confidence: 99%
“…3 Barrett, Levell and Milligan (2013) compare the performance of household expenditure surveys across countries and conclude that growing inequality contributed to declining coverage rates. This suggests that, if anything, expenditure coverage may be lower for younger cohorts, who have tended to be more unequal than their predecessors (see Section 2.2).…”
Section: Levels Of Income Spending and Savingmentioning
confidence: 99%
“…acknowledges support from the ESRC through the ESRC-funded Centre for Microeconomic Analysis of Public Policy at the Institute for Fiscal Studies (CPP, reference RES-544-28-5001). Barrett et al (2014) report that over a similar period, the Australian and Canadian budget surveys also experienced a fall in response rates but that those falls started later and were not accompanied by a decline in the coverage of national accounts consumption. 2 Readers are referred to Deaton (1992) for a discussion of some of the issues in constructing a measure of consumption.…”
Section: Acknowledgmentsmentioning
confidence: 96%
“…In some (but not all) countries, response rates are falling, and the correspondence between national budget survey data and national accounts data is deteriorating (Krueger et al 2010, Barrett et al 2014. For example, for the period 1986-2007, Barrett et al (2014) report that the response rate to the CE fell by 11 percentage points (to 74%) and to the FES by 17 percentage points (to 53%) and that the coverage of a national accounts-based measure of consumption fell by 13 percentage points for the CE (to 71%) and by 16 percentage points (to 67%) for the FES. Recent research on the CE has demonstrated that nonresponse in that survey is differential by income, with very high-income households being underrepresented.…”
Section: )?mentioning
confidence: 99%